Ultrastructure of hyperfunctioning parathyroid glands: Does it explain various patterns of 99mTc-sestamibi uptake - Elgazzar, Abdelhamid; Anim, Jehoran; Dannoon, Shorouk; Farghaly, Medhat (World Journal of Nuclear Medicine, 2017)
The aim of this study was to correlate the uptake of 99mTc-methoxy-isobutyl-isonitrile (MIBI) with ultra-structural features of parathyroid adenomas. Twenty patients with proven primary hyperparathyroidism were evaluated prospectively. Preoperative double-phase 99mTc-MIBI scintigraphy was performed in all patients and the degree of tracer uptake by the parathyroid lesions was assessed visually and semi-quantitatively. The excised glands were examined histologically and ultrastructurally, and their features were correlated with the degree of the radiotracer uptake. At surgery, 21 parathyroid adenomas were removed (double adenoma in one patient and a solitary adenoma in each of the remaining 19 patients). 99mTc-MIBI scan detected 18 of the 21 adenomas. There was positive correlation between the degree of 99mTc-MIBI uptake and the mitochondrial contents of the parathyroid adenoma cells. Four adenomas with intense uptake had high content of mitochondria in the cells. The three false-negative scans had low-to-moderate mitochondrial content. 99mTc-MIBI uptake is related to the mitochondrial content of the parathyroid adenoma cells.
Keywords: 99mTc- methoxy-isobutyl-isonitrile; electron microscopy; mitochondria; parathyroid adenoma; radionuclide